Modern Aspects of Formation Social Activity of Pupils in the Training Future teacher of Initial Classes - Hamzayev, Xaqnazar (Журнал Педагогики и психологии в современном образовании, 2021)
In this article discussec questions linked with training future primary grade teachers and developing this system of the formation social activity of students